2012
DOI: 10.1080/14786451.2011.637112
|View full text |Cite
|
Sign up to set email alerts
|

Clean development mechanism as a solution to the present world energy problems and a new world order: a review

Abstract: One of the important responses of Kyoto Protocol towards mitigation of global warming is the clean development mechanism (CDM) that has garnered large emphasis amidst the global carbon market in terms of certified emission reduction (CER). CERs are the carbon credits issued by the CDM executive board for emission reductions achieved by CDM projects and verified by designated operational entity (DOE) under the rules of the Kyoto Protocol. While CDM aims to achieve sustainable development in energy production an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Table 1 presents the articles reviewed. (Gupta & Mason, 2016) (Bodansky & Rajamani, 2013) (Ventura, et al, 2015) (Stewart, et al, 2013) (Moncel & Asselt, 2012) (Otto, et al, 2014) (Marcucci & Turton, 2013) (Kriegler, et al, 2015) (Riahi, et al, 2015) (Arroyo-Currás, et al, 2015) (Briner & Prag, 2013) (Chaturvedi, 2015) (Glomsrød, et al, 2013) (Gilley & Kinsella, 2015) Carbon tax 10 (Strand, 2013) (Alton, et al, 2014) (Wang & Li, 2015) (Gale, et al, 2013) ) (Elliott & Fullerton, 2013) (Sundar, et al, 2016) (Brooks, 2015) (Pezzey & Jotzo, 2013) (Lamperti, et al, 2015) Emission trading, trade, carbon markets 10 (Perthuis & Trotignon, 2013) (Uddin & Holtedahl, 2013) (Anon., 2013) ) (Lutz, et al, 2013) (Rabe, 2016) (Stiglitz, 2015) (Cormier, 2013) (Erickson, et al, 2014) (Sreekanth, et al, 2014) Carbon tax and cap-and trade 5 (Goulder & Schein, 2013) (Lui, 2016) (Sewalk, 2013) (Repetto, 2013) Minilateralism 8 (Debaere, et al, 2014) (Falkner, 2015) (Hjerpe & Nasiritousi, 2015) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 presents the articles reviewed. (Gupta & Mason, 2016) (Bodansky & Rajamani, 2013) (Ventura, et al, 2015) (Stewart, et al, 2013) (Moncel & Asselt, 2012) (Otto, et al, 2014) (Marcucci & Turton, 2013) (Kriegler, et al, 2015) (Riahi, et al, 2015) (Arroyo-Currás, et al, 2015) (Briner & Prag, 2013) (Chaturvedi, 2015) (Glomsrød, et al, 2013) (Gilley & Kinsella, 2015) Carbon tax 10 (Strand, 2013) (Alton, et al, 2014) (Wang & Li, 2015) (Gale, et al, 2013) ) (Elliott & Fullerton, 2013) (Sundar, et al, 2016) (Brooks, 2015) (Pezzey & Jotzo, 2013) (Lamperti, et al, 2015) Emission trading, trade, carbon markets 10 (Perthuis & Trotignon, 2013) (Uddin & Holtedahl, 2013) (Anon., 2013) ) (Lutz, et al, 2013) (Rabe, 2016) (Stiglitz, 2015) (Cormier, 2013) (Erickson, et al, 2014) (Sreekanth, et al, 2014) Carbon tax and cap-and trade 5 (Goulder & Schein, 2013) (Lui, 2016) (Sewalk, 2013) (Repetto, 2013) Minilateralism 8 (Debaere, et al, 2014) (Falkner, 2015) (Hjerpe & Nasiritousi, 2015) …”
Section: Resultsmentioning
confidence: 99%
“…He found that the unison global carbon market would be desirable, but also utopist with the current policies. Also Sreekanth et al (2014) came into the conclusion that even if the CDM does not necessarily contribute the sustainable development it is the most significant tool for climate change mitigation. He claimed that the CDM in spite of its flaws is a necessity for getting closer to reaching the emission reduction target.…”
Section: Market Based Approachmentioning
confidence: 99%
See 1 more Smart Citation